Principal Leadership and Organizational Culture on Teacher Performance in Public High School Banda Aceh - Musdiani Musdiani; Helminsyah Helminsyah; Lili Kasmini; Mukhlisuddin Mukhlisuddin; Syatria Adymas Pranajaya (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of principal leadership and organizational culture on teacher performance in public high schools in Banda Aceh, Indonesia, where Islamic values are embedded within educational governance and daily school practices. Employing a qualitative multiple-case study design, data were collected from sixteen public high schools through semi-structured interviews with principals and teachers, direct observations, and document analysis. To enhance the validity and trustworthiness of the findings, methodological and source triangulation were applied by systematically comparing evidence across data sources and participant groups. The findings reveal that principal leadership significantly influences teacher performance, particularly when leadership practices are participative, instructional, and grounded in Islamic ethical principles such as musyawarah (consultative decision-making), amanah (trust), and collective responsibility. Organizational culture was found to mediate this relationship by fostering collaboration, professional commitment, and instructional innovation. Schools characterized by a strong collaborative culture and consistent integration of Islamic values demonstrated higher teacher motivation, discipline, and engagement than schools with more hierarchical organizational structures. This study contributes to contemporary educational leadership literature by providing empirical evidence from a Sharia-based public education context, demonstrating that Islamic values can function as ethical and motivational resources that strengthen leadership effectiveness and organizational culture. The findings offer practical implications for educational leaders and policymakers in Aceh by highlighting the importance of integrating faith-based values with participative leadership practices to enhance teacher performance and school effectiveness.